Awareness of adolescent friendly health clinics among youth in Western Rajasthan: a pilot study - Dara, Sanjeeta; Arora, Smriti; Bhardwaj, Pankaj (International Journal Of Community Medicine And Public Health, 2025)
Background: Adolescent Friendly Health Clinics (AFHCs) were established to address the unique health needs of adolescents, offering services related to physical, mental, and reproductive health. However, limited awareness among youth may hinder their utilization. The objective was to assess the level of awareness regarding AFHCs among adolescents and to sources of information among adolescents regarding AFHCs. Methods: A cross-sectional pilot study was conducted among 50 adolescents from a school in Barmer district, Rajasthan, using a structured questionnaire. Data were analyzed using descriptive statistics to evaluate awareness and its sources. Results: Only 28% of participants were aware of AFHCs. Teachers were the most common source of information (18%), followed by healthcare workers (6%) and family members (2%). The majority of adolescents had no knowledge of AFHCs (72%), despite having educated parents and access to schools. Conclusions: Awareness about AFHCs among adolescents remains critically low. Targeted interventions involving schools, healthcare providers, and families are essential to bridge this gap.